Characterization of pain-related behaviors and gene expression profiling of peripheral sensory ganglia in a mouse model of acute ankle sprain - Pan, Yushuang; Hu, Qimiao; Yang, Yunqin; Nie, Huimin; Yin, Chengyu; Wei, Huina; Tai, Yan; Liu, Boyu; Shen, Zui; He, Xiaofen; Fang, Jianqiao; Liu, Boyi (Frontiers in Behavioral Neuroscience, 2023)
Introduction Lateral ankle sprain (LAS) is a very common type of joint injury. It occurred with high incidence among general population and especially among individuals participating sports and outdoor activities. A certain proportion of individuals who once developed LAS may suffer persistent ankle pain that affects daily activities. However, the mechanisms underlying LAS-induced pain still remained largely unknown. Methods We established a LAS mouse model and systematically evaluated the pain-related behaviors in this mouse model. RNA sequencing (RNA-Seq), combined with bioinformatics analysis, was undertaken to explore gene expression profiles. Immunostaining was used to study glial cell and neuron activation in ipsilateral spinal cord dorsal horn (SCDH) of LAS model mice. Ibuprofen was used to treat LAS model mice. Results The LAS model mice developed obvious signs of mechanical and heat hypersensitivities as well as gait impairments in ipsilateral hind paws. Besides, LAS model mice developed signs of pain-related emotional disorder, including pain-induced aversion. By RNA-Seq, we were able to identify certain differentially expressed genes and signaling pathways that might contribute to pain mechanisms of LAS mouse model. In addition, LAS model mice showed increased c-Fos and p-ERK immunoreactivity as well as astrocyte and microglia overactivation in ipsilateral spinal cord dorsal horn, indicating central sensitization might occur. Finally, LAS model mice respond to ibuprofen, a drug clinically used to treat ankle sprain pain. Conclusion Our study found LAS model mice may be used as a preclinical animal model for screening novel targets or therapies for ankle sprain. Thus, the study may further help to understand molecular mechanisms contributing to ankle sprain-induced pain.